The Influence of Religiosity and Mutual Cooperation on Organizational Commitment - Didi Sutisna; Yunita Endra Megiati; Noor Komari Pratiwi; Dian Novita; Rizki Rizkyatul Basir (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the influence of religiosity and mutual cooperation on lecturers' organizational commitment, as well as the role of mutual cooperation as a mediator of religiosity, and to assess the quality of the model formed. A quantitative research design with a survey method was used to collect data from 163 lecturers at 13 Health Sciences Colleges in Jakarta. Data analysis was performed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results show that mutual cooperation and religiosity have a significant direct influence on lecturers' organizational commitment. Additionally, religiosity also has an indirect effect through mutual cooperation. These findings underscore the importance of mutual cooperation in creating a harmonious work environment, supporting collaboration, facilitating professional growth, and building an inclusive organizational culture. The practical implications of this study suggest that higher education institution management can design programs to enhance lecturers' organizational commitment by focusing on mutual cooperation and religiosity.